The Early Neolithic of the Eastern Fertile Crescent Excavations at Bestansur and Shimshara, Iraqi Kurdistan - Raheem, Kamal Rasheed; Matthews, Wendy; Richardson, Amy; Matthews, Roger (Oxbow Books, 2020)
The Eastern Fertile Crescent region of western Iran and eastern Iraq hosted major developments in the transition from hunter-forager to farmer-herder lifestyles through the Early Neolithic period, 10,000-7000 BC. Within the scope of the Central Zagros Archaeological Project, excavations have been conducted since 2012 at two Early Neolithic sites in the Kurdistan region of Iraq: Bestansur and Shimshara. Bestansur represents an early stage in the transition to sedentary, farming life, where the inhabitants pursued a mixed strategy of hunting, foraging, herding and cultivating, maximizing the new opportunities afforded by the warmer, wetter climate of the Early Holocene. They also constructed substantial buildings of mudbrick, including a major building with a minimum of 65 human individuals, mainly infants, buried under its floor in association with hundreds of beads. These human remains provide new insights into mortuary practices, demography, diet and disease.